Results of continuous passive movement method application in physical rehabilitation process of patients with knee joint pathology - Оlexander Korolkov; Pavlо Bolkhovitin; Anastasia Korolkova; Nasr Al-Kali (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to evaluate the effectiveness of physical rehabilitation of patients with pathology of knee joints (KJ) in the postoperative period using the method of continuous passive movement in the joints with the help of domestic devices. Material & Methods: a comparative analysis of the results of rehabilitation of two clinical groups of patients was carried out, which were identical by sex, age, type of pathology and type of surgical interventions (52 male and 37 female), at the age of 18 to 60 years with the pathology of KJ who were on inpatient treatment. In the postoperative period, patients of the 2nd group, in addition to standard rehabilitation measures, performed passive development of motions in the affected KJ with the help of domestic devices for automatic development of movements. Result: program of physical rehabilitation of patients with KJ pathology, which consists of several stages, is based on the comprehensive application of a wide range of rehabilitation means with an individual approach to the course of the postoperative period in each particular patient. Conclusion: high efficiency of the use of the developed domestic devices for the automatic development of movements in the joints in the process of complex regenerative treatment of patients with the CS pathology, that allows recommending them for wide introduction in clinical use in rehabilitation centers and orthopedic and traumatological departments are proved.